Factors Affecting the Efficiency of Wooden Glue Beams Reinforced With Steel Rods - Makhmatkulov, T.; Boltaev, T.; Isrofilov, Z. (European Journal of Life Safety and Stability (2660-9630), 2022)
Glued wooden beams reinforced with steel rods have a number of advantages. Therefore, the use in large-span buildings gives a good economic effect. The article provides information that ensures their effectiveness.